“Don’t Know What You’ve Got Till It’s Gone”: Does the Disinvestment in America’s Libraries Signal the End of Civil Society? - Hall, Tracie (Maine Policy Review, 2024)
What is happening with public libraries in the United States and the United Kingdom though born of different origin stories—the former, book banning and the simultaneous devaluing of intellectual activity and public education; the latter, Brexit austerity measures and the resulting increased privatization of formerly public services and space—is having the same fiscal chilling effect. Communities are being deprived of the vital library and information services they rely on for continuous learning, economic mobility, and informed civic engagement.